Avalia??o de indicadores de sa?de materno-infantil de munic?pios priorit?rios para redu??o da mortalidade infantil no Estado da Bahia - Xavier, Aline Lima (2013)
Introduction: In recent decades, the Brazilian government has invested in the care of both mother and child through programs and policies in order to reduce maternal mortality rates and infant. These rates have been decreasing in Brazil, being a reflection of the organization of health services in the logic of integrated care. The complexity of the health sector gives room for permanent evaluation, and analysis of relevant health indicators, as they contain important information about the health status, system performance, as well as the actions taken and their ultimate impacts. Objective: To evaluate indicators of maternal and child health in Primary Health Care (PHC) in priority municipalities for the reduce child mortality of the state of Bahia in the period 2000-2012. Method: study series, directed to evaluating indicators of 33 municipalities in Bahia classified as priority. Data collection was performed at the DATASUS website , through the Health Information Systems, and the database consists of the indicators that represent the following variables: Process indicators of prenatal care (coverage , tetanus vaccination and monitoring home), and child care in the first year of life (childcare, exclusive breastfeeding, immunization and weight monitoring) ; outcome indicators of prenatal care (low birth weight , prematurity, prenatal consultations and type of delivery ) , and child care in the first and second year of life (malnutrition , acute respiratory infection and diarrhea ) and Indicators of infant and neonatal mortality . We conducted a descriptive analysis of indicators by municipality and regions, and used the simple linear regression model to check the trend over the period investigated, using a significance level of 5 %. Results: process indicators, except for the proportion of children under one year who had heavy decrease in 58% of municipalities, showed an increasing linear trend was statistically significant (p ? 0.05) in most of the cities studied, indicating an improvement in access to prenatal and monitoring of children in the first year of life. Regarding outcome indicators, low birth weight showed slight increase , the proportion of preterm births decreased , however some counties showed significant increase , especially large ones , and the proportion of cesarean section showed increasing trend (p < 0,0001) in most municipalities , which is consistent with the trend of the country ( 52 % ). In child care, both the proportion of malnutrition in children under 01 years the incidence of diarrhea and Acute Respiratory Infection (ARI) in children under 02 years, showed a statistically significant decrease, with the exception of 07 counties that showed increased morbidity due to ARI. Finally, the infant mortality rates fell evidence, similar to the situation in Brazil. However, neonatal, yet there was increase in almost half of the municipalities studied. Conclusion: The assessment of maternal and child care in priority municipalities in the last 13 years had rates that indicate the quality of health care , the need to strengthen the APS and building networks of attention.